Tracking the Autumn Migration of the Bar-Headed Goose (Anser indicus) with Satellite Telemetry and Relationship to Environmental Conditions. (16th October 2011) - Zhang, Yaonan; Hao, Meiyu; Takekawa, John Y.; Lei, Fumin; Yan, Baoping; Prosser, Diann J.; Douglas, David C.; Xing, Zhi; Newman, Scott H.
Abstract : The autumn migration routes of bar-headed geese captured before the 2008 breeding season at Qinghai Lake, China, were documented using satellite tracking data. To assess how the migration strategies of bar-headed geese are influenced by environmental conditions, the relationship between migratory routes, temperatures, and vegetation coverage at stopovers sites estimated with the Normalized Difference Vegetation Index (NDVI) were analyzed. Our results showed that there were four typical migration routes in autumn with variation in timing among individuals in start and end times and in total migration and stopover duration. The observed variation may be related to habitat type and other environmental conditions along the routes. On average, these birds traveled about 1300 to 1500 km, refueled at three to six stopover sites and migrated for 73 to 83 days. The majority of the habitat types at stopover sites were lake, marsh, and shoal wetlands, with use of some mountainous regions, and farmland areas.